Analysis of Creative Thinking Skills In Solving Story Problems In Solid Figure - Hasnawati, Zakiyah; Sutarni, Sri (Universitas Wiralodra, 2024)
This study aims to describe the creative thinking ability of students in solving story problems of solid figure. The method used is descriptive qualitative. The subjects of this study were 3 students of class VII SMP Negeri 1 Batu Sopang who were selected based on the test results and categorization of high, medium, and low levels of creative thinking. The results indicated that students with a high level of creative thinking ability achieved the fluency, originality, and elaboration indicators very well. While for the flexibility indicator the subject is still classified as good. Students whose level of creative thinking ability is moderate can achieve fluency and originality indicators well while for flexibility and elaboration indicators are still not good. Students whose level of creative thinking ability is low do not achieve all indicators of creative thinking.